أثر التدريس وفق نموذج بايبي للتعلم البنائي في اكتساب طالبات المرحلة الثانوية لمفاهيم مبحث البحث التربية الإسلامية في الأردن - الشرعة، ممدوح منيزل فليح; مصطفى، أماني شريف عيسى (الجامعة الأردنية - عمادة البحث العلمي, 2021)
This study aims to investigate the effect of teaching according to the Bybee model of constructive learning in the acquisition of high school students' concepts of Islamic education. Where he used descriptive statistics for this and test (T), arithmetic means, and standard deviations. The sample of the study consisted of (72) female high school students in Zarqa city, (34) experimental groups who were taught according to the Bybee model, and (38) female students of the control group studied traditionally. The model applied to two units of the Islamic Education Book for the first year of secondary science. The results of the study showed that there are alternative perceptions among high school students and that the questions related to the unit of Islamic jurisprudence obtained the highest percentages of alternative perceptions. The results also showed a statistically significant effect attributable to the method of teaching and in favor of the experimental group. The study concluded with some recommendations like training Islamic education teachers on the proper teaching strategies according to Bybee model.
هدفت هذه الدراسة إلى استقصاء أثر التدريس وفق نموذج بايبي للتعلم البنائي في اكتساب طالبات المرحلة الثانوية مفاهيم التربية الإسلامية. حيث استخدم الإحصاء الوصفي لذلك واختبار (ت) والمتوسطات الحسابية والانحرافات المعيارية. وبلغت عينة الدراسة من (72) طالبة من المدرسة الثانوية للإناث في مدينة الزرقاء، (34) مجموعة تجريبية تم تدريسهن وفق نموذج بايبي، و(38) طالبة المجموعة الضابطة درسن بالطريقة الاعتيادية. وطبق النموذج على وحدتين من كتاب التربية الإسلامية للصف الأول الثانوي العلمي. وأظهرت نتائج الدراسة وجود تصورات بديلة لدى طالبات المرحلة الثانوية وأن الأسئلة المتعلقة بوحدة الفقه الإسلامي حصلت على أعلى نسب مئوية للتصورات البديلة. كما أظهرت النتائج وجود أثر دال إحصائيا يعزى إلى طريقة التدريس ولصالح المجموعة التجريبية، وخلصت الدراسة بعدد من التوصيات منها تدريب معلمي التربية الإسلامية على استراتيجيات التدريس المناسبة وفقا لنموذج بايبي.
Keywords: التعليم الثانوي -- طلبة المرحلة الثانوية -- نموذج بايبي للتعلم البنائي -- التربية الإسلامية -- الأردن